Respon dua genotip kentang (Solanum tuberosum L.) dengan pemberian tiga sumber pupuk nitrogen di dataran medium - Anggi Handa Suwandi; Anis Rosyidah; Anis Sholihah (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
This study aimed to evaluate the growth and yield of two potato genotypes (S) due to three sources of nitrogen (G) fertilizer on medium plains. The study was arranged in a two-factor, randomized block design factorial and was repeated three times. The first factor is the source of N fertilizer, consisting of three levels: S1 = ZA ((NH4)2SO4), S2 = urea (CO(NH2)2), and S3 = ammonium nitrate (NH4NO3). The second factor was potato genotype, consisting of two levels G1 = MS 13 genotype and G2 = At 4 genotype. The data obtained were analyzed by F test at 5% level (ANOVA) to determine the effect of treatment and further LSD test was carried out to determine differences between treatments, and multiple regression analysis to determine the most influential factors on potato tuber starch content. The results showed that the highest starch content was obtained by the At 4 genotype of 18,50% and was suitable for medium plains. While the starch content of the MS 13 genotype was 17,53%. For fertilizing nitrogen sources, it is recommended to use ammonium nitrate, because it obtains the highest yield of 27,30 tons ha-1 from other nitrogen fertilizer sources.